Seasonal changes of mood, sleep and chronotypes, and the relation to sesonality - Adda Björk Ólafsdóttir 1984- (2022)
Background: Seasonality has been extensively studied in relation to various health problems, such as depressive symptoms and insomnia. It has been suggested to be mostly because of seasonal light, especially in Northern latitudes due to the large difference in light distribution between seasons. Light also governs the circadian rhythm, which is mainly controlled by biological systems but also by social and environmental factors. There is an association between evening chronotype, depression, and insomnia, mainly in relation to the winter months. This study aimed to assess if and how depression, insomnia and chronotypes changes between seasons and how that is related to participants own indication of seasonality. Methods: In an online survey, 222 participants completed self-report questionnaires about mood, seasonality, chronotype, and sleep. A Wilcoxon signed rank test, a Spearman’s rank-order correlation test and A Mann-Whitney U test were used to analyze the data. Results: ‘Morningness’ scores decreased significantly from summer to winter, while symptoms of insomnia and depression did not differ significantly between summer and winter. Higher percentiles of those meeting SAD criteria were seen in summer compared to winter. Sleep problems and seasonality, as well as depression and seasonality correlated significantly both in summer and winter. Seasonality and depressive symptoms were higher all year round in people who reported to be an evening type in summer. But when classifying people into morning and evening types by their reports in winter, there was no difference in seasonality or depression. This effect might be explained by a higher frequency of those defining themselves as either morning or evening types in summer (N=79) compared to winter (N=8). Conclusion: Evening types suffer from mood and sleep problems and higher seasonality throughout the year. However, in Iceland, chronotypes seem to disappear during the dark winter months, which suggests that chronotype is not necessarily a stable trait over ...